“I Can’t Stand Seeing Other People Having A Hard Time….”: Negotiating Identity And Participation As A Peer Supporter In Inclusive Learning - Nasywa Aprillia Dwiarti; Emy Sudarwati (LPPM Universitas PGRI Sumatera Barat, 2024)
There is a dearth of studies addressing how EFL students as peer supporters construct their identities and participate in assisting students with disabilities (SWD) in the process of learning completion in higher education. To fill this lacuna, the current narrative study explores how an Indonesian English student’s identity evolved over time as a result of her involvement as a peer supporter in inclusive learning. Data were garnered from a life history interview, and it was then analyzed using the temporal, personal-social, and place-based three-dimensional frameworks of narrative inquiry proposed by Clandinin and Connelly (2006). The analysis suggests that the participant in the current study gradually negotiated her identity in a challenging classroom and non-classroom environment that was influenced by time, personal-social, and geographical factors. The study also showed how the participant's experiences as a peer supporter for students with disabilities led to ongoing, enduring identity changes